Biosonar signal propagation in the harbor porpoise's (Phocoena phocoena) head: The role of various structures in the formation of the vertical beam - Wei, C.; Au, W.; Ketten, Darlene; Song, Z.; Zhang, Y. (Acoustical Society of America, 2017)
© 2017 Author(s). Harbor porpoises (Phocoena phocoena) use narrow band echolocation signals for detecting and locating prey and for spatial orientation. In this study, acoustic impedance values of tissues in the porpoise's head were calculated from computer tomography (CT) scan and the corresponding Hounsfield Units. A two-dimensional finite element model of the acoustic impedance was constructed based on CT scan data to simulate the acoustic propagation through the animal's head. The far field transmission beam pattern in the vertical plane and the waveforms of the receiving points around the forehead were compared with prior measurement results, the simulation results were qualitatively consistent with the measurement results. The role of the main structures in the head such as the air sacs, melon and skull in the acoustic propagation was investigated. The results showed that air sacs and skull are the major components to form the vertical beam. Additionally, both beam patterns and sound pressure of the sound waves through four positions deep inside the melon were demonstrated to show the role of the melon in the biosonar sound propagation processes in the vertical plane.